2004
DOI: 10.1539/joh.46.272
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Occupational Injuries for Various Jobs in Railway Workers: A Case‐Control Study

Abstract: Correlates of Occupational Injuries for Various Jobs in Railway Workers: A Case‐Control Study: Nearkasen Chau, et al. National Institute for Health and Medical Research (Inserm), Unit 420, Faculté de Medicine, France—Few studies have simultaneously addressed the role of occupational factors, individual characteristics and living conditions in occupational injuries, and to the best of our knowledge none on railway workers. This survey assessed the roles of these factors in various types of injuries and for vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
59
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 35 publications
7
59
1
3
Order By: Relevance
“…This study found that first years in present job were more strongly associated with fractures than all occupational injuries combined (adjusted OR 2.49 vs. 1.41, 95% CI 1.13-1.76 5) ) among the same railway workers. This factor also had a high but non-significant Could be multiple: 2.5% for construction workers and 9.7% for railway workers.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…This study found that first years in present job were more strongly associated with fractures than all occupational injuries combined (adjusted OR 2.49 vs. 1.41, 95% CI 1.13-1.76 5) ) among the same railway workers. This factor also had a high but non-significant Could be multiple: 2.5% for construction workers and 9.7% for railway workers.…”
Section: Discussionmentioning
confidence: 56%
“…Sleep disorders alter health status and work ability, and may lead to fatigue and altered risk perception which increase injuries 14) . No do-it-yourself and no gardening activity was found to be more strongly associated with fractures than with all occupational injuries combined (crude OR 1.82 vs. 1.28, 1.07-1.54 5) ) among the railway workers. This could be explained by the fact that these physical activities improve work ability and balance control 15) and that maintenance operators were especially affected by fractures.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations